Relación entre inteligencia emocional y bullying: revisión aplicada - Castillo Rivera, Mery Yeanella (2023)
Emotional intelligence is defined as the ability to accurately perceive, evaluate, and express emotions. Bullying is a social variable that has been explained from Vygotsky's ecological theory and social learning model. The aim of this work is to determine the relationship between emotional intelligence and bullying through the review of previous studies carried out in this field. A systematic search was carried out, according to the the PRISMA guidelines indications (Page et al., 2021), in the Scopus, Ebsco and SpringerLink databases. For the analysis, those studies that met the inclusion and exclusion criteria (n=10) were selected. The results showed that there is a statistically significant correlation between emotional intelligence and bullying. It can be concluded that emotional intelligence is a protective factor for bullying victims, aggressors and the educational community; Prevent suicidal risk and suicidal ideation, contribute to stress management, mitigate violent behavior in aggressors and promote the experimentation of positive emotions in adolescents.